Measuring Financial Efficiency of Insurance Companies in Indonesia Using Stochastic Frontier Analysis Approach: A Comparison Between Islamic and Conventional Insurances - Nur Kholis; Yunita Nur Afifah (Department of Islamic Economics, Islamic University of Indonesia, 2022)
This paper aims to analyze the efficiency value and compare the efficiency ratio between sharia insurance and conventional insurance companies, both life insurance and general insurance in Indonesia, for 2018-2020. The research applies the Stochastic Frontier Analysis (SFA) method, which uses total capital and expenses as input variables, and total income as output variables. The efficiency values of Islamic and conventional insurance companies' results were compared using an independent sample t-test statistical test. The population of this research is all Islamic and conventional insurance companies listed on the website of the Financial Services Authority (OJK). The sample used is 19 sharia insurance companies (15 life insurance companies and four general insurance companies). The sample of conventional insurance is 23 companies (22 life insurance companies and one general insurance company). The results showed that the efficiency value of Islamic insurance companies (0.6549) was 0.0697 lower than conventional insurance (0.7246). It can be concluded that the efficiency of conventional insurance is better than Islamic insurance. Islamic insurance management capabilities are lower than conventional insurance companies’ management capabilities.